Czynniki obecnej polityki światowej. ([S.l. : s.n.], 1946)
Afisz inf. o odczycie w wykonaniu Ludwika Gościńskiego w Sopocie 26.05.1946 r.
Keywords: Gościński, Ludwik -- (1890-1969).; Sopot (Polska) -- 1945-1970 -- druki ulotne